The Relationship Between Employment Factors and Perceived Job Performance Among Foreign Workers in Manufacturing Industry - Yap, Wen Xin; Ahmad, Nurazwa (Research in Management of Technology and Business, 2021)
Dependency of foreign worker employment in manufacturing sector affects the productivity of organization. There was an issue discussed about the availability, education level and working condition that may affect the foreign worker’s job performance. This study aims to determine the level of foreign worker employment factors and level of their job performance and to evaluate the relationship between employment factors and perceived job performance. A quantitative method was used in this research and the questionnaires were distributed to 364 respondents in manufacturing sector in Johor resulting to the responses rate of 13.74%. The data collected was analyzed by using Statistical Package for Social Science (SPSS) for descriptive analysis, reliability analysis, normality test, and correlation analysis. The results of descriptive analysis showed working condition was the main factor of foreign worker employment in manufacturing industry in Johor. Both availability and working condition of foreign workers had a significant relationship with perceived job performance. However, the education background did not have a significant relationship with perceived job performance. The findings may become as a reference to those companies in manufacturing sector to know the factors of foreign worker employment and their job performance.